An overview of recent developments in metabolomics and proteomics – phytotherapic research perspectives. Issue 1 (1st January 2017) - Mumtaz, Muhammad Waseem; Hamid, Azizah Abdul; Akhtar, Muhammad Tayyab; Anwar, Farooq; Rashid, Umer; AL-Zuaidy, Mizher Hezam
ABSTRACT: In recent years, medicinal plants have gained much attention as potential source of bioactives for the development of novel herbal drugs for primary healthcare. However, phytotherapeutic mechanisms of action of phytomedicines need to be explored comprehensively. Out of the available strategies for the said purpose, metabolomics is one, which results in the production of inclusive metabolite profiles providing a clear understanding of diagnostic changes in the levels of metabolites, leading to therapeutic monitoring of drug targets through the elucidation of metabolomic pathways. On the other hand, proteomics is also a powerful strategy to deal with systematic protein expression analysis and analyze different biomarkers compared to metabolomics during drug treatment. Currently, 1 H nuclear magnetic resonance spectroscopy, mass spectrometry (MS), Fourier transform infrared spectroscopy, gas chromatography equipped with mass spectrometry, liquid chromatography coupled with MS and ultra-performance liquid chromatography-MS coupled with multivariate statistical techniques, such as principle component analysis, partial least square and orthogonal-partial least square are among the widely applicable analytical tools for metabolite profiling, whereas two-dimensional electrophoresis and matrix-assisted laser desorption ionization time-of-flight -MS are the most accepted analytical methods for proteomic biomarker investigation. The present review summarizes the recent developments and perspectives of the biomarker investigation strategies so as to elaborate their imperative role for sustainable herbal drug developments.